Asphyxia while swallowing solid food caused by bronchial compression: a variant of the pneumonectomy syndrome. - Fong, K. M. (1994)
A 40 year old man presented with recurrent episodes of dyspnoea whilst swallowing solid food. He had undergone right pneumonectomy and thoracoplasty for recurrent pneumonias and empyema 23 years previously. Solid food boluses appeared to cause bronchial obstruction by compressing the surgically distorted left main bronchus. This is a new variant of the post pneumonectomy syndrome.